Sedentary lifestyle in middle-aged women is associated with severe menopausal symptoms and obesity. Issue 5 (May 2016) - Blümel, Juan E.; Fica, Juan; Chedraui, Peter; Mezones-Holguín, Edward; Zuñiga, María C.; Witis, Silvina; Vallejo, María S.; Tserotas, Konstantinos; Sánchez, Hugo; Onatra, William; Ojeda, Eliana; Mostajo, Desireé; et al.
Abstract: Objective: The aim of the study was to evaluate the association between sedentary lifestyle and the severity of menopausal symptoms and obesity in middle-aged women. Methods: The Menopause Rating Scale, the Goldberg Anxiety and Depression Scale, and the Athens Insomnia Scale were administered to 6, 079 Latin American women aged 40 to 59 years. Sedentary lifestyle was defined as fewer than three weekly, 30-minute periods of physical activity. Results: Sedentary women had more severe menopausal symptoms (total Menopause Rating Scale score: 9.57 ± 6.71 vs 8.01 ± 6.27 points, P  < 0.0001) and more depressive symptoms (Goldberg), anxiety (Goldberg), and insomnia (Athens Scale) compared with non-sedentary women. They also had greater mean waist circumference (86.2 ± 12.3 vs 84.3 ± 1.8 cm, P  < 0.0001) and a higher prevalence of obesity (20.9% vs 14.3%, P  < 0.0001). Logistic regression analysis showed that both obesity (odds ratio [OR] 1.52; 95% CI, 1.32-1.76) and severe menopausal symptoms (OR 1.28; 95% CI, 1.06-1.53), including insomnia and depressive mood, were positively associated with a sedentary lifestyle. Having a stable partner (OR 0.85; 95% CI, 0.76-0.96), using hormone therapy (OR 0.75; 95% CI, 0.64-0.87) and having a higher educational level (OR 0.66; 95% CI, 0.60-0.74) were negatively related to sedentary lifestyle. Conclusions: There was a high prevalence of sedentary lifestyle in this middle-aged Latin American female sample which was associated with more severe menopausal symptoms and obesity.